The sentimental education of the novel - Cohen, Margaret, 1958- (Princeton University Press, 1999)
"The nineteenth-century French novel has long been seen as the heroic production of great men, who confronted in their works the social consequences of the French Revolution. And it is true that French realism, especially as developed by Balzac and Stendhal, was one of the most influential novelistic forms ever invented. Margaret Cohen, however, challenges the traditional account of the genesis of realism by returning Balzac and Stendhal to the forgotten novelistic contexts of their time. Reconstructing a key formative period for the novel, she shows how realist codes emerged in a "hostile takeover" of a prestigious contemporary sentimental practice of the novel, which was almost completely dominated by women writers."--Jacket